1989
DOI: 10.1002/bjs.1800761016
|View full text |Cite
|
Sign up to set email alerts
|

Complications of parotid surgery: The need for selectivity

Abstract: The morbidity rate following 112 operations on the parotid gland is reported. Facial nerve palsy (temporary, 38 per cent; permanent, 9 per cent) and Frey's syndrome (11 per cent) were common following superficial parotidectomy. For pleomorphic adenoma and malignant lesions this procedure is justified. Benign conditions, which can be diagnosed preoperatively, should be treated by more limited surgery which has a lower complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
2

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 14 publications
1
44
0
2
Order By: Relevance
“…We are still waiting to see a consensus about its incidence, for in the publications we studied the incidence rate varied from 2 to 80% 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are still waiting to see a consensus about its incidence, for in the publications we studied the incidence rate varied from 2 to 80% 7 .…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the surgical technique employed in parotidectomies, because we see no report of FS in enucleating procedures. In cases of superficial parotidectomies, there are publications describing 4.4% rates, however such fact may be related to a lack of direct interviewing the patient, because the study is only descriptive 7,9 . Other reports, in which questionnaires and iodine tests were used to diagnose FS, show results varying from 36% to 50% 10,11,12 .…”
Section: Discussionmentioning
confidence: 99%
“…Owen ERTC et al reported most common complication to be facial nerve palsy (38%) followed by Frey's syndrome (11%) and fistula (2%). 10 …”
Section: Discussionmentioning
confidence: 99%
“…The instruments for aspiration consisted of a 10 ml disposable syringe filled with a 22G or 23G needle [27][28][29][30] . The skin at the site was wiped with an antiseptic and the suspected salivary gland swelling was held with one hand in a favourable position.…”
Section: Methodsmentioning
confidence: 99%